Effect of the Metal Ion on the Enantioselectivity and Linkage Isomerization of Thiosemicarbazone Helicates. Issue 20 (20th March 2017) - Romero, María J.; Suárez, Vanesa; Fernández‐Fariña, Sandra; Maneiro, Marcelino; Martínez‐Núñez, Emilio; Zaragoza, Guillermo; González‐Noya, Ana M.; Pedrido, Rosa
Abstract: The effect of the metal ion and ligand design on the enantioselectivity and linkage isomerization of neutral cobalt and zinc bisthiosemicarbazone metallohelicates has been investigated in this work. The electrochemical synthesis has afforded the enantioselective formation of chirally pure cobalt helicates, and the ΛΛ isomer of a single enantiomer has been crystallized as only product for the cobalt methyl‐substituted thiosemicarbazone helicate. Interestingly linkage isomers have been formed from zinc ethyl‐substituted thiosemicarbazone helicate enantiomers for the first time. The co‐existence of these isomers has been evaluated from the point of view of both experimental results and computational calculations. Abstract : Twister ! The electrochemical reaction of zinc and cobalt plates with bisthiosemicarbazone ligands gives rise to the enantioselective formation of chirally pure cobalt(II) helicates and a rare example of linkage isomerism in zinc(II) helicates.